Reflecting on God - Inzlicht, Michael; Tullett, Alexa M. (Psychological Science, 2010)
The world is a vast and complex place that can sometimes generate feelings of uncertainty and distress for its inhabitants. Although religion is associated with a sense of meaning and order, it remains unclear whether religious belief can actually cause people to feel less anxiety and distress. To test the anxiolytic power of religion, we conducted two experiments focusing on the error-related negativity (ERN)—a neural signal that arises from the anterior cingulate cortex and is associated with defensive responses to errors. The results indicate that for believers, conscious and nonconscious religious primes cause a decrease in ERN amplitude. In contrast, priming nonbelievers with religious concepts causes an increase in ERN amplitude. Overall, examining basic neurophysiological processes reveals the power of religion to act as a buffer against anxious reactions to self-generated, generic errors—but only for individuals who believe.